Introduction: Melting Point - Sérgio Henrique Faria (Mètode Science Studies Journal: Annual Review)
We might think that high mountain regions, being remote and frozen, would be naturally isolated and protected from human action – the last untouched corners of the planet. However, the truth is that high mountains are among the regions most vulnerable to climate change and most affected by it. As well as the general increase in temperatures and atmospheric pollution, complex climatic phenomena such as teleconnections, ice albedo feedback loops, altitude-dependent warming, and glacier response time amplify and accelerate changes in the world's frozen areas. For this reason, high mountains are also important natural laboratories for studying climate change due to their sensitivity to climate, their role in regulating regional hydrology and ecosystems, and their function within the global climate system.